Gonzalez, Francisco J. (2024): Human Life in Motion. Heidegger’s Unpublished Seminars on Aristotle as Preserved by Helene Weiss, Indiana University Press, Bloomington. - Campayo Villegas, Martín (Revista de Filosofía, 2024)
.